Genomic diversity, antimicrobial resistance and dissemination of Serratia marcescens complex in patients admitted to ICUs - Zhu, Wentao; Chen, Xi; Shen, Hong; Wei, Ming; Yang, Chunxia; Gu, Li (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundSerratia spp. is an important nosocomial pathogen, with increasing threat of antimicrobial resistance. We aimed to describe the population structure, antimicrobial resistance and dissemination of Serratia isolates in ICUs of China.MethodsSerratia spp. were isolated from patients admitted to ICUs of a large hospital between January 2014 and December 2024. Whole-genome and clinical data were collected to identify their epidemiological and evolutionary characteristics.Results106 Serratia isolates was divided into five species based on phylogenomic and ANI analyses, namely S. sarumanii, S. ureilytica, S. marcescens, S. bockelmannii, and S. nevei. The predominant ST was ST595 (12.3%), followed by ST525 (10.4%) and ST428 (4.7%), all of which belonged to S. sarumanii. Based on a 16 SNPs threshold, 15 distinct clusters and 44 singleton strains were identified, with the largest cluster circulating in five different ICUs over the past 11 years. Notably, most grouped isolates within each cluster were isolated from different ICUs, indicative of potential inter-ICU transmission. The unique genes significantly enriched within each species contributed to their niche adaptation and plasticity. Various beta-lactamase genes, such as blaCTX-M and blaOXA, were detected, along with carbapenemase genes including blaKPC-2 and blaNDM-5 in nine isolates.ConclusionThese results contribute to understanding the population structure and dissemination of Serratia spp. in ICUs, highlighting their ongoing evolution towards increasing resistance and outbreak potential.